Frequency and clinicopathological features of fibroelastotic changes in the gastrointestinal tract - Lichtmannegger, Ines; Gölder, Stefan; Probst, Andreas; Dönmez, Günay; Agaimy, Abbas; Langer, Erich; Müller, Wolfram; Zhang, Lanjing; Spatz, Hanno; Märkl, Bruno (Virchows Archiv : an international journal of pathology, 2014)
Fibroelastotic changes (FEC) and especially elastotic polyps of the gastrointestinal (GI) tract are considered rare benign lesions. They consist of accumulations of elastic fibers within the mucosal, submucosal, or muscular layer, occurring in all parts of the GI tract and often appearing as polyps, but also as diffuse non-polyp-forming deposits. They have been the subject of only a few studies. To explore the clinical and histopathological features of FEC in the GI tract, a series of 162 elastotic lesions was collected within a 2-year period. The clinical data and endoscopic findings were correlated. FEC appeared as polyp-forming lesions of the large intestine in 23 samples (14 %), all other samples concerning histological findings without an identifiable gross mass. Frequently related findings were postinterventional status (9 %), previous irradiation (7 %), and history of GI lymphoma (4 %). Eight samples (5 %) presented endoscopically with lesions justifying surgical intervention. We identified three different histological patterns of FEC, which we have called fibroelastosis, angioelastosis, and elastofibroma. Consistent with previous studies, CD34 immunohistochemical staining (performed on 38 polypoid FEC specimens) showed an increase of CD34-positive mesenchymal cells in 95 % of immunostained samples, suggesting a potential role for CD34-positive mesenchymal cells in the accumulation of elastic fibers. In conclusion, FEC are more common in the GI tract than previously recognized. They often present as a benign polyp. Many accompany other diseases like ulcers and atrophic gastritis or represent a residual finding after an intervention.